Megaric-Stoic Logic: Possibility and Necessity as Alethic Operators - Fernández Cuesta, José Alejandro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
In this article, we introduce a possible way to interpret the possibility and necessity notions developed within the Megaric-Stoic logic as alethic modal operators. Megaric-Stoic semantics will be introduced as metaphysical background for necessity and possibility definitions and arguments will be offered in order to give up the prevailing interpretations which include ad hoc variables. After proposing the survey of Diodorus definitions from relational modal semantics, a series of topics that deserve to be revisited from this perspective will be pointed out.